Antimicrobial Active Chitosan-Based Cotton Yarns: Effect of Chitosan Solution Concentration - Emilija Toshikj, Ognen Petrovski, Petrovska Milena, Jordanov Igor (University of Ljubljana, Faculty of Natural Sciences and Engineering, 2023)
Using the exhaustion-pad-dry-rinse method, chitosan was applied to alkaline-scoured and bleached cotton yarns in a solution with concentrations ranging from 0.2–1% to achieve good antimicrobial activity against the bacteria Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive). Studied samples were also assessed by measuring the amount of introduced chitosan, amount of accessible amino groups, mechanical properties, whiteness index and the b* colour coordinate. Alkaline-scoured and bleached cotton yarns treated with all concentrations of the chitosan solution showed good antimicrobial activity against Escherichia coli and Staphylococcus aureus. Better antimicrobial activity was achieved against Escherichia coli. Increasing the concentration of chitosan solution deteriorated the mechanical properties of chitosan-treated cotton yarns. The optimal concentration of chitosan solution incorporated in the exhaustion phase to obtain chitosan-treated yarns with good antimicrobial activity and mechanical properties was 0.6%. The best antimicrobial treatment should minimise potential economic costs while providing functionality.
Keywords: cotton, chitosan, antimicrobial activity, Escherichia coli bacteria, Staphylococcus aureus bacteria